The Use of GPS in Tuna Fishing Operations by the Rimoi Fishermen's Group Towards Efficient and Effective Tuna Fishing Operations - Umar Tangke; Aisyah Bafagih; Ruslan Laisouw; Srifani Jainudin; Aninda M. Hi. Saleh; Mardiana Yusuf (JURNAL SAINS SOSIAL DAN HUMANIORA (JSSH), 2025)
This article examines the use of GPS technology by the Rimoi fishing community on Ternate Island to improve the efficiency and effectiveness of tuna fishing operations. GPS technology serves as a navigation tool that makes it easier for fishermen to determine fishing locations more accurately and quickly, thereby reducing search time and operational costs, including fuel consumption. After training in GPS use, fishermen were able to systematically mark productive locations, which previously depended on experience and traditional methods. The results of implementation showed an increase in catch of around 30% and an increase in income of 20% in the first two months of GPS use. In addition to increasing productivity, the use of GPS also contributes to improved sailing safety by reducing the risk of poor navigation. This approach supports the sustainability of fishing businesses by optimizing resources and improving data-based work patterns. In conclusion, GPS integration has proven to be an effective solution in improving the economic and safety aspects of fishing, while supporting sustainable marine resource management.